Proceedings of the 2nd ACM Conference on Bioinformatics, Computational Biology and Biomedicine 2011
DOI: 10.1145/2147805.2147849
|View full text |Cite
|
Sign up to set email alerts
|

Ranking differential genes in co-expression networks

Abstract: Identifying the genes that change between two conditions, such as normal versus cancer, is a crucial task in understanding the causes of diseases. Differential networking has emerged as a powerful approach to achieve this task and to detect the changes in the corresponding network structures. The goal of differential networking is to identify the differentially connected genes between two networks. However, the current differential networking methods primarily depend on pair-wise comparisons of the genes based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…We also compare our method with any combinations of two gene regulatory network inference methods and two differential regulatory detection methods. Based on benchmarking literature of gene regulatory network inference from single-cell data 16 and differential regulatory network detection 14 , we choose GENIE3 17 and PIDC 18 as methods for network inference, and choose diffK 19 and diffRank 20 as methods for network comparison. The results showed that our method outperforms all those methods (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We also compare our method with any combinations of two gene regulatory network inference methods and two differential regulatory detection methods. Based on benchmarking literature of gene regulatory network inference from single-cell data 16 and differential regulatory network detection 14 , we choose GENIE3 17 and PIDC 18 as methods for network inference, and choose diffK 19 and diffRank 20 as methods for network comparison. The results showed that our method outperforms all those methods (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, using single-cell ATAC-seq, patterns of gene expression can be combined with chromatin accessibility profiles, thus identifying cell subpopulations and groups of cells at different developmental stages [ 124 ]. Consequently, several differential network analysis algorithms have been developed, such as DiffRank [ 125 ], dcanr R package [ 126 ], DiffK [ 127 ], DINA [ 128 ], to name a few. We refer the reader to [ 129 ] for a statistical perspective of DiNA and [ 130 ] for a DiNA algorithm comparison.…”
Section: Grn Validationmentioning
confidence: 99%